Literary Discourse on Quranic Studies: A Historical Study on The Model of Literary Interpretation to The Quran - Fitriansyah, Nuzul (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2022)
Abstract: The aspect of the beauty of language ('ijaz lughawi) is one of the first miracles that emerged from the Qur'an. This aligns with the audience to whom the Qur'an was revealed around 14 centuries ago: people who are very close to the literary tradition. Interestingly, scholars of the Qur'an, from classical to contemporary, see this as an opportunity for studies and still developing and producing various monumental works. Through this paper, the author tries to trace chronologically how the Al-Qur'an and literature meet to become an approach in interpreting the Al-Qur'an. The research in this paper is carried out through essential matters by looking at how the Qur'an was revealed in Arab society, the interpretation practices carried out by the Prophet and his companions, to the contact of the Qur'an with modern literature. This study uses a socio-historical approach by looking at the macro-cultural context of early Arab society and the process of interpretation of the earlier era carried out by the Prophet, companions and tabi'in. This study argues that the emergence of a model of literary interpretation of the Qur'an is closely related to the traditions and culture of Arab society, which are close to literary traditions. Furthermore, this research contributes to the history of interpretation, especially in tracking the various approaches that appear in the study of the Quran.Abstrak: Aspek keindahan bahasa ('ijaz lughawi) merupakan salah satu keajaiban pertama yang muncul dari al-Qur'an. Hal ini sejalan dengan khalayak yang diwahyukan Al-Qur'an sekitar 14 abad yang lalu: orang-orang yang sangat dekat dengan tradisi sastra. Menariknya, para sarjana Al-Qur'an, dari klasik hingga kontemporer, melihat hal ini sebagai peluang untuk mengkaji dan tetap mengembangkan serta menghasilkan berbagai karya monumental. Melalui tulisan ini, penulis mencoba menelusuri secara kronologis bagaimana Al-Qur'an dan sastra bertemu untuk menjadi sebuah pendekatan dalam menafsirkan Al-Qur'an. Kajian dalam tulisan ini dilakukan melalui hal-hal esensial dengan melihat bagaimana Alquran diturunkan di masyarakat Arab, praktik tafsir yang dilakukan Nabi dan para sahabat, hingga kontak Alquran dengan sastra modern. Kajian ini menggunakan pendekatan sosio-historis dengan melihat konteks makro-budaya masyarakat Arab awal dan proses interpretasi era awal yang dilakukan oleh Nabi, sahabat dan tabi'in. Kajian ini berargumen bahwa munculnya model tafsir sastra al-Qur'an sangat erat kaitannya dengan tradisi dan budaya masyarakat Arab yang dekat dengan tradisi sastra. Lebih jauh lagi, penelitian ini memberikan kontribusi terhadap sejarah tafsir, khususnya dalam menelusuri berbagai pendekatan yang muncul dalam kajian al-Qur'an.